2006
DOI: 10.1016/j.mseb.2005.09.061
|View full text |Cite
|
Sign up to set email alerts
|

The colour of ochres explained by their composition

Abstract: International audienceThe first purpose of this paper is to underline a relevant colorimetric co-ordinate characterizing the colour of ochres within their extremely wide range, from pale yellow to dark red. The second purpose is to link together quantitatively the variations of this colorimetric co-ordinate and the various chemical compositions of the samples, mainly hematite, goethite and white pigments. A group of 30 modern ochres and a group of 20 ancient ochres have been investigated. All these natural pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
122
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(154 citation statements)
references
References 17 publications
23
122
1
8
Order By: Relevance
“…However, it is not only elemental composition that determines the colour of ochre. 52 Mineralogical and elemental composition and structural morphology, including grain size and crystallography, also influence colourimetric properties. 17 It has been demonstrated that different ochre processing techniques result in differences in pigment powder consistency and colour 48 -an observation confirmed in this study.…”
Section: Colourimetrymentioning
confidence: 99%
“…However, it is not only elemental composition that determines the colour of ochre. 52 Mineralogical and elemental composition and structural morphology, including grain size and crystallography, also influence colourimetric properties. 17 It has been demonstrated that different ochre processing techniques result in differences in pigment powder consistency and colour 48 -an observation confirmed in this study.…”
Section: Colourimetrymentioning
confidence: 99%
“…Mutual analogies within natural earths and giallolinos are evident and can be ascribed to the same basic chemical composition. The yellow ochre was mainly constituted of hydrated iron oxide (goethite), as evidenced by comparison with the pure goethite SRF [15] .…”
Section: Pre-irradiation Analysesmentioning
confidence: 87%
“…But the variation in their colors can be explained by their composition. Table 2 shows a clear relation between color of ochre and the concentration of iron oxides in the sample (Elias et al, 2006).…”
Section: Physico-chemical Observationmentioning
confidence: 92%